Inside Cover: Mn−O Covalency Governs the Intrinsic Activity of Co‐Mn Spinel Oxides for Boosted Peroxymonosulfate Activation (Angew. Chem. Int. Ed. 1/2021). Issue 1 (12th November 2020) - Guo, Zhi‐Yan; Li, Chen‐Xuan; Gao, Miao; Han, Xiao; Zhang, Ying‐Jie; Zhang, Wen‐Jun; Li, Wen‐Wei
Abstract : Bimetallic spinel oxides are efficient catalysts for peroxymonosulfate (PMS) activation but the catalytic mechanism is unclear. The critical role of Mn−O covalency in determining the intrinsic activity of Co3−x Mnx O4 and a new mechanism of Co–Mn synergy are revealed by Wen‐Wei Li and co‐workers in their Research Article on page 274 . Co strengthens Mn−O covalency in the octahedral configuration of Co3−x Mnx O4, which lowers the charge transfer energy of the MnOh –PMS interaction and drastically accelerates Mn VI /Mn III redox cycling.